DAMPAK UKURAN PERUSAHAAN, PROFITABILITAS DAN LEVERAGE TERHADAP MANAJEMEN LABA - Manik, Triva Maria; Putra, Dios Nugraha; Tarmizi, Tashadi; Rumodhon, Berliansyah (Magister Ilmu Akuntansi Universitas Jambi, 2025)
The purpose of this study is to understand and examine the relationship between the impact of company size, profitability and leverage on earnings management. This study aims to examine the industry consisting of 95 food and beverage industries listed on the Indonesia Stock Exchange, and 43 industries were selected as samples using purposive sampling technique. The data was collected through the Indonesia Stock Exchange source, and using the official website of each industry. This research method uses a quantitative approach, involving descriptive statistics, classiﬁcation assumption tests and multiple regression analysis tests using SPSS version 24. From the results of the study, it was found that company size has a significant negative impact on earnings management, profitability, which uses the ROA proxy, has a significant positive impact on earnings management, and leverage, which uses the DER proxy, has no impact on earnings management.